PERILAKU KESELAMATAN KERJA KARYAWAN - Eldes Willy Filatrovi (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2019)
The aim of this study is to analyse the effect of Safety Climate, Work Satisfaction and Safety Motivation that influences the employee Safety Behavior at employee APAC Manufacture in Indonesia. The study involved 200 employees as the questionnaire respondents from 4 department production APAC manufacturing company. Simple random sampling was use at quantitative research with a proportional quantity of responden have taken in every department depend on total employee in each department. The validation of qualitative result have used by honest validation from respondens which was confirmated and approved by responden’s with their signature at qualitative question and answer list. Based on the result of The Safety Climate is positive and significant influence to the Safety Motivation The Work Satisfaction is positive and significant influence to the Safety Motivation, The Safety Climate is positive and significant influence to the Safety Behavior, The Work Satisfaction is not influence to the Safety Behavior and The Safety Motivation is positive and significant to the Safety Behavior